Granular Computing: At the Junction of Rough Sets and Fuzzy Sets - Bello, Rafael (Springer, 2017)
Since their very inception, both fuzzy and rough set theories have earned a sound, well-deserved reputation owing to their intrinsic capabilities to model uncertainty coming from the real world. The increasing amount of investigations on both subjects reported every year in the literature vouches for the dynamics of the area and its rapid advancements.